A study on the effectiveness of promotion mix activities practiced by Pusat Zakat Melaka and impacts on zakat collection in Malacca / Norzilla Mohammad Aripin - Mohammad Aripin, Norzilla (Faculty of Business and Management, 2011)
Marketing is an element that very important to ensure the successful of a financial institution. This is related to the promotional mix that is including advertising, sales promotion, personal selling and public relation. The promotions are important elements in a financial institution to gain profit. Promotional mix will help an organization or any financial institutions to bring their product and services to the market. Customer satisfaction also is important for an organization to keep customers and enhance customers’ retention. This study evaluates the effectiveness of the promotion mix activities practiced by Pusat Zakat Melaka and the impacts on zakat collection in Malacca. Most of customers prefer pay zakat and the activities will influencing the customers to pay the zakat at Pusat Zakat Melaka. This study focusses on the effectiveness of promotion mix activities that the PZM do to attracting the customers. For the purpose of this report, primary and secondary data have been used in the process of data collection. Information was collected through primary sources such as do the survey on the customers perception by interview and so on, will the secondary sources such as journals and internet.